INCIDENCE OF AXILLARY RECURRENCE AFTER NEGATIVE SENTINEL LYMPH NODE BIOPSY IN A RETROSPECTIVE COHORT OF BREAST CANCER PATIENTS - Vieira, Sabas Carlos; Barros, Letícia Rodrigues; Oliveira, Lucas Moura de; Miranda, Luja de Carvalho; Araújo, Natália Rebeca Alves de (Mastology, 2020)
Introduction: Breast cancer is the second most common cancer in the world, and the most common among women, spreading especially to the axillary lymph nodes. The axillary status is the main prognostic factor, and the sentinel lymph node biopsy (SLNB) technique is incorporated to surgical treatment. Objectives: To analyze cases of recurrence in patients with breast carcinoma after being submitted to negative SLNB. Methods: Observational, retrospective study carried out from 1999 to 2019 in a clinic in Teresina. We analyzed the cases of axillary recurrence after negative SLNB in a cohort comprised of 459 patients. The study was approved in the Research Ethics Committee, report n. 2.817.502. Results: There were two cases of axillary recurrence after negative SLNB. CASE 1: 77 year-old patient with infiltrating carcinoma of no special type in the left breast, measuring 2.2 cm (T2N0M0) - IIA. She was submitted to sectorectomy with SLNB, which was negative. Immunohistochemical: ER+, PR-, HER2 -, P53+, KI-67+ 70%, luminal B. She received radiotherapy on the bre-ast and did not undergo hormone therapy. After four years, she presented local recurrence and was treated with segmen-tal resection and axillary lymph node dissection. The histological analysis of the surgical specimen showed infiltrating carcinoma of no special type, measuring 1.5cm, with perineural invasion, and 4 axillary lymph node without neoplasm. She received adjuvant hormone therapy with tamoxifen. The patient was followed up for 40 months after the procedures and was free of disease, and then she was no longer being followed-up. CASE 2: 50-year old patient with invasive lobular carcinoma (right breast), submitted to sectorectomy with negative SLNB. She received postoperative radiotherapy and hormone therapy. Immunohistochemical: ER+ 90%, PR+ 90%, HER2-, KI-67+ 60%. After two years of follow-up, she pre-sented with right axillary recurrence, and underwent axillary lymph node dissection, with 13 resected lymph nodes, of which one presented metastasis. She began on hormone therapy with anastrozole. Nowadays, 37 months after surgery, she has no evidence of recurrence. Conclusion: In this study, the rate of axillary recurrence after negative SLNB was 0.43%.